(untitled) (Bangladesh Journal of Microbiology, 2023)
Costus speciosus (J. Koenig) Sm., commonly known as crepe ginger, is primarily used as an ornamental plant worldwide. The aim of this research was to study the phytoconstituents of locally collected C. speciosus plant samples and test their antimicrobial effect against selected bacterial strains. Phytochemical analysis showed the presence of alkaloids, flavonoids, steroids, phenolic compounds, tannins, glycosides, and cardiac glycosides in the extracts. The extracts displayed variable degrees of antibacterial activity against the microorganisms in a bioautography experiment based on thin-layer chromatography. All the extracts showed activity against S. aureus, and none showed any activity against P. aeuroginosa. The ethanol and ethyl acetate extracts from the plant leaf and stem showed efficacy against S. typhi and B. subtilis, while the ethyl acetate extracts prevented the growth of S. pneumoniae. Only the ethanol extract from plant leaves had a negligible effect on K. pneumoniae. Bangladesh J Microbiol, Volume 39, Number 2, December 2022, pp 46-52